MACROSCOPIC ANALYSIS OF INCISION WOUND HEALING IN WHITE RATS TREATED WITH PLATELET-RICH PLASMA DERIVED FROM PORCINE BLOOD - Raharja, Made Sandy Widhi; Wirata, I Wayan; Kendran, Anak Agung Sagung; Sudisma, I Gusti Ngurah; Gorda, I Wayan; Berata, I Ketut (Buletin Veteriner Udayana, 2025)
Platelet-rich plasma (PRP) has been identified as a potential therapeutic agent to mitigate factors that impede healing. PRP, which is enriched with growth factors, plays a critical role in accelerating tissue regeneration across various stages of wound repair. This study aimed to investigate the effects of PRP derived from porcine blood on the healing of incisional wounds in white rats (Rattus norvegicus). Macroscopic parameters, including wound length, wound color, moisture levels, and crust formation, were evaluated. The study employed an experimental design, utilizing a split-time completely randomized design (CRD) with statistical analysis. The results demonstrated significant improvements in wound closure, as evidenced by reduced wound length, accelerated changes in wound color, maintained wound moisture leading to faster drying, and enhanced crust formation, all of which contributed to a reduction in wound size (P < 0.05). These findings indicate that PRP derived from porcine blood significantly accelerates the healing process of incisional wounds in white rats, as reflected by macroscopic healing indicators. Further research is recommended to determine the optimal shelf life of PRP to ensure its efficacy and stability during prolonged storage, thereby supporting its sustainable clinical application.